Sistem Pakar Penentuan Minat Dan Bakat Anak Umur 5-10 Tahun - Adistya, Merry C. S.; Wibowo, Januar; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2012)
Parent always want to give the best things for their children. But sometimes, they force their children about their want, so it can cause some conflict between parent and their children. This can makes their children feel despressed, lost of study spirit and makes schooling laziness. An expert system using of talent and interest determining can help parent to understand their children is talent and interest so they can give appropriate education for their children depend of talent and interest. This system use forward change method that using facts and characteristic of the children to produce talent and inters result